2013
DOI: 10.1080/13691058.2012.762119
|View full text |Cite
|
Sign up to set email alerts
|

Factors contributing to inconsistent condom use among heterosexual men in Curaçao

Abstract: This study explored, from a public health perspective, factors that contribute to inconsistent condom use by men in Curaçao through semi-structured face-to-face interviews with 21 heterosexual men. The findings show that there is an important disconnect between what is considered culturally appropriate sexual behaviour for men and women and condom use, that diverging from prescribed notions of masculinity and femininity in order to use condoms consistently is difficult, and that condom use is particularly prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 17 publications
2
9
0
Order By: Relevance
“…Two separate qualitative studies of Ugandan men found that men’s status among peers depended on having multiple women sexual partners (64, 103). Other studies echo this idea that more women sexual partners usually signifies greater social standing (74, 79, 90, 102, 104109). Ethnographic research with both Australian military men and working-class British youth found that men shared with peers only masculine-promoting details of their sexual experiences with women (or lied about them) to maximize status gains (65, 89).…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Two separate qualitative studies of Ugandan men found that men’s status among peers depended on having multiple women sexual partners (64, 103). Other studies echo this idea that more women sexual partners usually signifies greater social standing (74, 79, 90, 102, 104109). Ethnographic research with both Australian military men and working-class British youth found that men shared with peers only masculine-promoting details of their sexual experiences with women (or lied about them) to maximize status gains (65, 89).…”
Section: Introductionmentioning
confidence: 90%
“…Because of this, participants frequently claimed that, in ‘the heat of the moment’, they do not think of using a condom: ‘At that moment, you have other priorities. Sensibility disappears and you don’t think about the consequences of your actions.’” (74)(p. 422–423) This discourse connects maleness with insatiable sexual desire for women and, thus, a real man in this context is impulsive and irrational.…”
Section: Introductionmentioning
confidence: 99%
“…There are many factors contributing in condom use, such as: cultural, HIV and STI transmission, condom providing and also partner or clients involvement. (13,14) A research in Ghana, Kenya, Tanzania and Zambia showed that condom use affect by its availability and easy access to free condom. (15,16) Other reasons can explain why the subjects not used the condom were: had sex with regular partners or boyfriends, partners rejected to use a condom, uncomfortable reason and had alcohol drunk.…”
Section: Discussionmentioning
confidence: 99%
“…Norms of masculinity across cultures can facilitate HIV transmission by encouraging sexual risk behaviours, such as the having of multiple sexual partners (Bowleg et al 2011; Shearer et al 2005; Gage 2008), and discouraging HIV protective behaviours, such as consistent condom use (Flood 2003; Stutterheim et al 2013; Santana et al 2006. In his foundational Theory of Gender and Health, Courtenay (2000) describes how men use their behaviours, including sexual behaviours, to enact their masculinity among friends, who then evaluate the social value of those behaviours.…”
Section: Introductionmentioning
confidence: 99%